Musings on Firewalls and the Information Paradox - Michael Devin (Galaxies, 2014)
The past year has seen an explosion of new and old ideas about black hole physics. Prior to the firewall paper, the dominant picture was the thermofield model apparently implied by anti-de Sitter conformal field theory duality. While some seek a narrow responce to Almheiri, Marolf, Polchinski, and Sully (AMPS) , there are a number of competing models. One problem in the field is the ambiguity of the competing proposals. Some are equivalent while others incompatible. This paper will attempt to define and classify a few models representative of the current discussions.